Sustained dominance of South Asia’s black carbon pollution impacting the Tibetan plateau in the 21st century - Hao Deng; Zhenming Ji; Shichang Kang; Qianggong Zhang; Zhiyuan Cong; Wenjie Dong (npj Climate and Atmospheric Science, 2024)
Abstract Black carbon (BC) not only warms the atmosphere but also accelerates glacier melt over the Tibetan Plateau (TP), threatening the Asia Water Tower. In order to understand future BC change in the TP, we analyzed the distribution of BC over the TP and its surroundings from 1985 to 2014, as well as under the SSP585 and SSP245 scenarios from 2015 to 2100, utilizing bias-corrected CMIP6 data to drive the regional climate model. BC concentration showed a continuous decrease under both SSP585 and SSP245 scenarios, yet the contribution of BC from South Asia to the TP’s BC steadily increased over time, reaching approximately 87% by the end of the 21st century. The maximum increased contribution was observed in the southeastern part of the TP, gradually decreasing towards the northwest. As the slower rate of BC reduction in South Asia compared to other regions, and the significant decrease in average wind speed over the TP in the future, the contribution of BC from South Asia to the TP has increased despite BC emission reductions. The threat of BC from South Asia on the security of the Asian water tower and the surrounding climate environment persists in the 21st Century.